Enantiopure hydroxymethylated cycloalkenols as privileged small molecular multifunctional scaffolds for the asymmetric synthesis of carbocycles. Issue 11 (1st July 2016) - Kumar, Rajan; Rej, Rohan Kalyan; Halder, Joydev; Mandal, Haridas; Nanda, Samik
Graphical abstract: Abstract: Enantiopure hydroxymethylated cycloalkenols bearing a quaternary stereocenter have been synthesized by a Pybox mediated enantioselective desymmetrization method. The synthesized cycloalkenols serve as starting precursors for the construction of several chiral small ring carbocyclic frameworks by a distinct functional group transformation. Abstract : ( R )-2-(Hydroxymethyl)-2-methylpent-4-enyl benzoate: C14 H18 O3 [ α ]D 28 = +5.2 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (2 R ) Abstract : ( R )-2-((4-Methoxybenzyloxy)methyl)-2-methylpent-4-enyl benzoate: C22 H26 O4 [ α ]D 28 = +6.8 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (2 R ) Abstract : ( S )-2-((4-Methoxybenzyloxy)methyl)-2-methylpent-4-en-1-ol: C15 H22 O3 [ α ]D 28 = −4.2 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (2 S ) Abstract : (1 S, 5 R )-5-((4-Methoxybenzyloxy)methyl)-5-methylcyclopent-2-enol: C15 H20 O3 [ α ]D 28 = +24.6 ( c 0.5, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 5 R ) Abstract : (1 S, 5 R )-5-(Hydroxymethyl)-5-methylcyclopent-2-enol: C7 H12 O2 [ α ]D 28 = +48.8 ( c 0.6, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 5 R ) Abstract : (1 R, 5 R )-5-((4-Methoxybenzyloxy)methyl)-5-methylcyclopent-2-enol: C15 H20 O3 [ α ]D 28 = +73.2 ( c 1.2, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 5 R ) Abstract : (1 R, 5 R )-5-(Hydroxymethyl)-5-methylcyclopent-2-enol: C7 H12 O2 [ α ]D 28 = +42.2 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 5 R ) Abstract : ( S )-2-(( tert -Butyldiphenylsilyloxy)methyl)-2-methylpent-4-enyl benzoate: C30 H36 O3 Si [ α ]D 28 = +10.2 ( c 0.5, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (2 S ) Abstract : ( S )-2-(( tert -Butyldiphenylsilyloxy)methyl)-2-methylpent-4-en-1-ol: C23 H32 O2 Si [ α ]D 28 = +6.8 ( c 0.3, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (2 S ) Abstract : ( R )-2-((4-Methoxybenzyloxy)methyl)-2-methylpent-4-en-1-ol: C15 H22 O3 [ α ]D 28 = +4.6 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (2 R ) Abstract : (1 S, 6 R )-6-((4-Methoxybenzyloxy)methyl)-6-methylcyclohex-3-enol: C16 H22 O3 [ α ]D 28 = +22.8 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 6 R ) Abstract : (1 R, 6 R )-6-((4-Methoxybenzyloxy)methyl)-6-methylcyclohex-3-enol: C16 H22 O3 [ α ]D 28 = +58.8 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 6 R ) Abstract : (1 R, 2 R, 3 R, 4 R )-4-((4-Methoxybenzyloxy)methyl)-4-methylcyclopentane-1, 2, 3-triol: C15 H22 O5 [ α ]D 28 = +33.8 ( c 1.2, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 2 R, 3 R, 4 R ) Abstract : (1 S, 2 S, 3 R, 4 R )-4-((4-Methoxybenzyloxy)methyl)-4-methylcyclopentane-1, 2, 3-triol: C15 H22 O5 [ α ]D 28 = −12.8 ( c 0.5, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 4 R ) Abstract : (1 R, 2 R, 3 R, 5 S )-3-((4-Methoxybenzyloxy)methyl)-3-methyl-6-oxabicyclo[3.1.0]hexan-2-ol: C15 H20 O4 [ α ]D 28 = −23.9 ( c 0.5, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 2 R, 3 R, 5 S ) Abstract : (1 S, 2 R, 3 R, 4 R )-4-((4-Methoxybenzyloxy)methyl)-4-methylcyclopentane-1, 2, 3-triol: C15 H22 O5 [ α ]D 28 = +16.8 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 R, 3 R, 4 R ) Abstract : tert -Butyl((1 S, 5 R )-5-((4-methoxybenzyloxy)methyl)-5-methylcyclopent-2-enyloxy)dimethylsilane: C21 H34 O3 Si [ α ]D 28 = +55.4 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 5 R ) Abstract : (1 R, 2 R, 3 R, 4 R )-3-( tert -Butyldimethylsilyloxy)-4-((4-methoxybenzyloxy)methyl)-4-methylcyclopentane-1, 2-diol: C21 H36 O5 Si [ α ]D 28 = +10.8 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 2 R, 3 R, 4 R ) Abstract : (1 S, 2 S, 3 R, 4 R )-3-( tert -Butyldimethylsilyloxy)-4-((4-methoxybenzyloxy)methyl)-4-methylcyclopentane-1, 2-diol: C21 H36 O5 Si [ α ]D 28 = +38.8 ( c 1.2, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 4 R ) Abstract : tert -Butyl((3a R, 4 R, 5 R, 6a R )-5-((4-methoxybenzyloxy)methyl)-2, 2, 5-trimethyltetrahydro-3a H -openta[ d ][1, 3]dioxol-4-yloxy)dimethylsilane: C24 H40 O5 Si [ α ]D 28 = +22.6 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a R, 4 R, 5 R, 6a R ) Abstract : ((3a R, 4 R, 5 R, 6a R )-4-( tert -Butyldimethylsilyloxy)-2, 2, 5-trimethyltetrahydro-3a H -clopenta[ d ][1, 3]dioxol-5-yl)methanol: C16 H32 O4 Si [ α ]D 28 = +44.2 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a R, 4 R, 5 R, 6a R ) Abstract : tert -Butyldimethyl((3a R, 4 R, 5 R, 6a R )-2, 2, 5-trimethyl-5-vinyltetrahydro-3a H -cyclopenta[ d ][1, 3]dioxol-4-yloxy)silane: C17 H32 O3 Si [ α ]D 28 = +8.7 ( c 0.4, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a R, 4 R, 5 R, 6a R ) Abstract : (3a R, 4 R, 5 R, 6a R )-4-(Allyloxy)-2, 2, 5-trimethyl-5-vinyltetrahydro-3a H -cyclopenta[ d ][1, 3]dioxole: C14 H22 O3 [ α ]D 28 = −12.6 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a R, 4 R, 5 R, 6a R ) Abstract : ((3 R, 4 S, 4a S, 6 R, 7 R, 7a R )-4a-Methyloctahydrocyclopenta[ b ]pyran-3, 4, 6, 7-tetrayl tetraacetatel: C17 H24 O9 [ α ]D 28 = +78.2 ( c 1.2, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3 R, 4 S, 4a S, 6 R, 7 R, 7a R ) Abstract : (1 S, 2 S, 3 R, 5 S )-3-((4-Methoxybenzyloxy)methyl)-3-methylbicyclo[3.1.0]hexan-2-ol: C16 H22 O3 [ α ]D 28 = −23.8 ( c 0.4, MeOH) source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 5 S ) Abstract : tert -Butyl((1 S, 2 S, 3 R, 5 S )-3-((4-methoxybenzyloxy)methyl)-3-methylbicyclo[3.1.0]hexan-2-yloxy)dimethylsilane: C22 H36 O3 Si [ α ]D 28 = −32.6 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 5 S ) Abstract : ((1 S, 2 S, 3 R, 5 S )-2-( tert -Butyldimethylsilyloxy)-3-methylbicyclo[3.1.0]hexan-3-yl)methanol: C14 H28 O2 Si [ α ]D 28 = −22.8 ( c 0.5, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 5 S ) Abstract : tert -Butyldimethyl((1 S, 2 S, 3 R, 5 S )-3-methyl-3-vinylbicyclo[3.1.0]hexan-2-yloxy)silane: C15 H28 OSi [ α ]D 28 = −17.8 ( c 1.2, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 5 S ) Abstract : (1 S, 2 S, 3 R, 5 S )-3-Methyl-3-vinylbicyclo[3.1.0]hexan-2-ol: C9 H14 O [ α ]D 28 = −12.2 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 5 S ) Abstract : (1 S, 2 S, 3 R, 5 S )-2-(Allyloxy)-3-methyl-3-vinylbicyclo[3.1.0]hexane: C12 H18 O [ α ]D 28 = −29.8 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 R, 5 S ) Abstract : (1 S, 3 S, 4 R, 6 R )-4-((4-Methoxybenzyloxy)methyl)-4-methyl-7-oxabicyclo[4.1.0]heptan-3-ol: C16 H22 O4 [ α ]D 28 = +13.8 ( c 0.3, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 3 S, 4 R, 6 R ) Abstract : (1 R, 3 S, 4 R, 6 S )-4-((4-Methoxybenzyloxy)methyl)-4-methyl-7-oxabicyclo[4.1.0]heptan-3-ol: C16 H22 O4 [ α ]D 28 = −18.2 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 3 S, 4 R, 6 S ) Abstract : (1 S, 2 S, 4 S, 5 R )-5-(Hydroxymethyl)-5-methylcyclohexane-1, 2, 4-triol: C8 H16 O4 [ α ]D 28 = +33.5 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 S, 2 S, 4 S, 5 R ) Abstract : (1 S, 4 R, 6 S )-4-((4-Methoxybenzyloxy)methyl)-4-methylbicyclo[4.1.0]heptan-3-ol: C17 H24 O3 [ α ]D 28 = −28.0 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 3 S, 4 R, 6 S ) Abstract : tert -Butyl((1 S, 6 R )-6-((4-Methoxybenzyloxy)methyl)-6-methylcyclohex-3-enyloxy)dimethylsilane: C22 H36 O3 Si [ α ]D 28 = +38.8 ( c 0.9, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: 1 S, 6 R Abstract : (1 S, 2 R, 4 R, 5 S )-5-( tert -Butyldimethylsilyloxy)-4-((4-methoxybenzyloxy)methyl)-4-methylcyclohexane-1, 2-diol: C22 H38 O5 Si [ α ]D 28 = +44.2 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: 1 S, 2 R, 4 R, 5 S Abstract : (1 S, 2 R, 4 R, 5 S )-5-( tert -Butyldimethylsilyloxy)-4-((4-methoxybenzyloxy)methyl)-4-methylcyclohexane-1, 2-diol: C22 H38 O5 Si [ α ]D 28 = +32.8 ( c 0.6, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (1 R, 2 S, 4 R, 5 S ) Abstract : tert-Butyl((3a S, 5 S, 6 R, 7a R )-6-((4-methoxybenzyloxy)methyl)-2, 2, 6-trimethylhexahydrobenzo[ d ][1, 3]dioxol-5-methylsilane: C25 H42 O5 Si [ α ]D 28 = +23.8 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a S, 5 S, 6 R, 7a R ) Abstract : ((3a R, 5 R, 6 S, 7a S )-6-( tert -Butyldimethylsilyloxy)-2, 2, 5-trimethylhexahydrobenzo[ d ][1, 3]dioxol-5-yl)methanol: C17 H34 O4 Si [ α ]D 28 = +22.8 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a R, 5 R, 6 S, 7a S ) Abstract : tert -Butyldimethyl((3a S, 5 S, 6 R, 7a R )-2, 2, 6-trimethyl-6-vinylhexahydrobenzo[ d ][1, 3]dioxol-5-yloxy)silane: C18 H34 O3 Si [ α ]D 28 = +12.4 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a S, 5 S, 6 R, 7a R ) Abstract : (3a S, 5 S, 6 R, 7a R )-2, 2, 6-Trimethyl-6-vinylhexahydrobenzo[ d ][1, 3]dioxol-5-ol: C12 H20 O3 [ α ]D 28 = +8.6 ( c 0.6, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a S, 5 S, 6 R, 7a R ) Abstract : (3a R, 5 R, 6 S, 7a S )-6-(Allyloxy)-2, 2, 5-trimethyl-5-vinylhexahydrobenzo[ d ][1, 3]dioxole: C15 H24 O3 [ α ]D 28 = +25.4 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a R, 5 R, 6 S, 7a S ) Abstract : (3a S, 4a S, 8a R, 9a R )-2, 2, 8a-Trimethyl-4, 4a, 6, 8a, 9, 9a-hexahydro-3a H -[1, 3]dioxolo[4, 5- g ]chromene: C13 H20 O3 [ α ]D 28 = +38.2 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a S, 4a S, 8a R, 9a R ) Abstract : (3a S, 4a S, 7 R, 8 S, 8a R, 9a R )-2, 2, 8a-Trimethyloctahydro-3a H -[1, 3]dioxolo[4, 5- g ]chromene-7, 8-diol: C13 H22O5 [ α ]D 28 = +44.2 ( c 0.8, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3a S, 4a S, 7 R, 8 S, 8a R, 9a R ) Abstract : (3 R, 4 S, 4a R, 6 R, 7 S, 8a S )-4a-Methyloctahydro-2 H -chromene-3, 4, 6, 7-tetraol: C10 H18 O5 [ α ]D 28 = +69.2 ( c 1.0, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: (3 R, 4 S, 4a R, 6 R, 7 S, 8a S )